Impairment of fetal hematopoietic stem cell function in the absence of Fancd2 - Suzuki, Sakiko (Exp Hematol, 2016)
Fanconi Anemia (FA), results from mutations in genes necessary for DNA damage repair and often leads to progressive bone marrow failure. Although the exhaustion of the bone marrow leads to cytopenias in FA patients as they age, evidence from human FA and mouse model fetal livers suggests hematopoietic defects originate in utero which may lead to deficient seeding of the bone marrow. To address this possibility, we examined the consequences of loss of Fancd2, a central component of the FA pathway. Examination of E14.5 Fancd2 knockout (KO) fetal livers showed a decrease in total cellularity and specific declines in long-term and short-term hematopoietic stem cell (LT- and ST-HSC) numbers. Fancd2 KO fetal liver cells display similar functional defects to Fancd2 adult bone marrow cells including reduced colony forming units, increased mitomycin C sensitivity, increased LT-HSC apoptosis and heavily impaired competitive repopulation, implying these defects are intrinsic to the fetal liver and not dependent on the accumulation of DNA damage during aging. Telomere shortening, an aging-related mechanism proposed to contribute to HSC apoptosis and bone marrow failure in FA, was not observed in Fancd2 KO fetal livers. In summary, loss of Fancd2 yields significant defects to fetal liver hematopoiesis, particularly the HSC population, which mimic key phenotypes from adult Fancd2 KO bone marrow independent of aging-accrued DNA damage.